The effect of aquatic and treadmill exercise in individuals with chronic stroke - Patrícia Martins Franciulli; Aline Bigongiari; Juliana Valente Francica Grilletti; Flávia de Andrade e Souza Mazuchi; Alberto Carlos Amadio; Luis Mochizuki (Universidade de São Paulo, 2019)
ABSTRACT We compared the effect of gait training on treadmill versus deep water on balance and gait in 12 ischemic stroke chronic survivors randomly sorted to the Pool or Treadmill Groups. Berg Scale (BBS) and timed up and go test (TUG) were applied before and after the interventions. Just one person applied all tests and she was blinded for the aims of the study. Surface EMG of the paretic and non-paretic (NP) side muscles were recorded during walking on a treadmill. Three 100-ms epochs were extracted from the EMG related to gait phases: weight acceptance; propulsion; and pre-strike. For each epoch, we calculated the RMS of the EMG signal. Participants did gait training for 9 weeks (3 times/week, 40 minutes/session). The Pool group did the deep-water walking with a swimming belt. The Treadmill group walked on the treadmill at the maximum speed they could stand. The Manova group compared the effect of training, group, side, muscles, and gait phase into the EMG. Anova was used to test the effect of training, group side, and gait phase into BBS, TUG and EMG variables. Pool and Treadmill had increased balance and agility. The highest EMG RMS occurred at the paretic side, for the Treadmill and after training. The mm. tibialis anterior, gastrocnemius lateralis, vastus lateralis, and biceps femoris presented the highest RMS for the NP side; while for mm. rectus femoris and semitendinosus, the paretic side presented the highest RMS. Thus, the both types of exercise lead to similar functional adaptations with different muscular activations during walking.